2013
DOI: 10.2320/matertrans.m2013018
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Mechanical and Electrical Properties on the Sintered Ni–50 mass% Cr Alloys by HIP Treatment

Abstract: This study investigated Ni50 mass% Cr alloys produced by the vacuum sintering and hot isostatic pressing (HIP) of powder metallurgy technology. The experimental results showed that the relative density of Ni50 mass% Cr alloys reached 98.67%, the apparent porosity decreased to 1.33%, transverse rupture strength (TRS) increased to 454.29 MPa and electrical resistivity decreased to 4.284 © 10 ¹4 ³·cm after 1345°C sintering for 1 h. Meanwhile, laminar eutectic precipitations appeared in the sintered Ni50 mass% Cr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…Previous literature also revealed a positive relationship between the hardness and the relative density. 6,8) The hardness was signi cantly enhanced as the sintering density increased. The literature also shows that decreasing the porosities of sintered materials effectively enhances plastic deformation resistance and hardness.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature also revealed a positive relationship between the hardness and the relative density. 6,8) The hardness was signi cantly enhanced as the sintering density increased. The literature also shows that decreasing the porosities of sintered materials effectively enhances plastic deformation resistance and hardness.…”
Section: )mentioning
confidence: 99%
“…Conventional P/M involves mixing the metal powders, compacting of the mixed powders into molds and then sintering of the compact powders under the different atmospheres. 6,7) P/M technology is the conventional process for the production of Cr-Ni alloys. On the other hand, hot-press sintering technique as a common technique was performed to fabricate the bulk bodies of the alloys.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the NbC and Ti reaction and transform to TiC after sintering process. ICMSNT 2017 6 On the other hand, the SEM morphology observations of NbC-1, NbC-3 and NbC-5 specimens by vacuum sintering at 1275°C for 1 h, as shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…Powder metallurgy (P/M) methods offer various types of materials with the objective of achieving higher strength, hardness and wear resistance for composite materials such as titanium-based alloys powders. Conventional P/M involves mixing the metal powders, compacting of the mixed powders into moulds and then sintering of the compact powders under the different atmospheres [6,7]. Furthermore, our previous study has shown that the combination of these elements in a Ti-8Mo-6Ni alloy has a good balance between mechanical properties and hot workability [2].…”
Section: Introductionmentioning
confidence: 99%
“…7) Conventional P/M involves mixing the metal powders, compacting of the mixed powders into molds and then sintering of the compact powders under the different atmospheres. 9,10) One of the advantages of P/M compared to other methods is having better control on the microstructure, where better distribution of the reinforcements is possible in P/M compacts.…”
Section: Introductionmentioning
confidence: 99%